The International Covenant on Economic, Social and Cultural Rights: a perspective on its development - Craven, Matthew C. R. (1992)
The International Covenant on Economic, Social and Cultural Rights entered currently has 118 States Parties and has been in force for 17 years. Over the past five years, the implementation of the Covenant has come under the supervision of the Committee on Economic, Social and Cultural Rights. Unlike its predecessort, the Sessional W orking Group, the Committee has taken its supervisory role seriously such that it has begun to develop both the substance of the Covenant and the implementation procedures. This study, based principally upon the work of the Committee on Economic, Social and Cultural Rights, discusses a number of aspects in which the substance of the Covenant and its supervision procedures may be seen to have been developed. Chapter 1 traces the roots of economic, social and cultural rights and outlines their codification in the Universal Declaration of Human Rights, and later the Covenant, following the end of the Second World War. Significant aspects of the drafting process are analysed in detail. Chapter 2 discussest he nature and scope of the State obligations under the Covenant as regards the implementation of the rights. Particular emphasis is given to the terms of article 2(1) and how they have been interpreted in the work of the Committee. Chapter 3 analyses, primarily from a theoretical standpoint, the manner and degree to which the terms of the Covenant may be given "direct effect", or in other words, relied upon directly in domestic courts. Chapters 4 to 8 address particular articles within the Covenant and considers the interpretation given to them by the Committee. Chapter 4 deals with article 2(2) (and to a lesser extent article 3) concerning non-discrimination; Chapter 5 deals with article 6 concerning the right to work; Chapter 6 deals with article 7 regarding the right to just and favourable conditions of work; Chapter 7 deals with article 8 concerning rights related to trade unions; and Chapter 8 deals with article 11 concerning the right to an adequate standard of living and, in particular, the rights to food and housing. In each case, an attempt is made to evaluate the Committee's approach to each article and assess the possibilities for future development. Chapter 9 addresses the emergence, role and working methods, of the Committee as a human rights supervisory body. Particular consideration is also given to the problems encountered and the Committee's future prospects. Chapter 10, as the concluding chapter, draws together the observations made in earlier chapters and attempts to make an evaluation of the present and future utility of the Covenant as a mechanism for the promotion and protection of economic, social and cultural rights.